Migration and jihadi terrorism in Europe - Kuntić, Dario (Teorija in praksa, 2021)
This article aims to answer the research question of whether a relationship exists between migration and jihadi terrorism in Europe. The core argument is that increased migration from mainly Muslim countries has added to the risk of jihadi terrorism in European countries. The phenomena of homegrown extremism within immigrant communities, the cross-border movement of radicalised individuals, and the return of foreign fighters have all raised the likelihood of Islamic terrorism in Europe. The research results suggest that while migrants coming from terrorist-prone states are an important vehicle through which terrorism is manifested and diffused, there is an even bigger threat of jihadi terrorism from radicalised individuals within European immigrant communities.
Keywords: Džihad; Emigration and immigration; Izseljevanje in priseljevanje; Jihad; migracije; radikalizacija; Terorizem; Terrorism